If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+3-(18-2x)=2x+5
We move all terms to the left:
4x+3-(18-2x)-(2x+5)=0
We add all the numbers together, and all the variables
4x-(-2x+18)-(2x+5)+3=0
We get rid of parentheses
4x+2x-2x-18-5+3=0
We add all the numbers together, and all the variables
4x-20=0
We move all terms containing x to the left, all other terms to the right
4x=20
x=20/4
x=5
| 2.25t+5=13.5t+14* | | 14−2u=−12 | | 19+3x=100 | | 60z+12=25z+46z-10 | | 2.3x-(1.6)=8.8-(2.9x) | | 4=20-4j | | 15x^2+8x-76=0 | | 6y-8=6y-99+6y-59 | | 15x^2+9x-76=0 | | -6x+2(2x+21)=52 | | 3x-30+2x=25 | | 3x^2-12=54 | | -2s+194=s-6+2s-15 | | -4x-3(-4x-3)=-63 | | 9z–-11=38 | | V=x(14-2x)(12-2x) | | -x-9/15=11/15 | | -3x-7(2x+2)=88 | | 9z—-11=38 | | -90=6x+2(-5x-21) | | 20x+0.20x=30x+0.15x | | -40=4x-4(5x-22) | | 2p+6=p-3p+34 | | 103=2x+5(-3x-8) | | 13=-6b+-11 | | -5x+4(7x-16)=166 | | 16=8(u-90) | | -85=5x+5(x-3) | | 2=w/6-2 | | -4x+4(7x+11)=-100 | | 3x-(5)=-2x+10 | | 4x-5x+9=6x-9 |